Implementation of Faith-Based Full Day School Program at SD YKPP Pendopo - Zainubi, Zainubi; Annur, Saipul; Yuniar, Yuniar (Universitas Pendidikan Mandalika, 2025)
Along with technological advancements and the ease of internet access through mobile phones, people of all ages—from children to adults—often use them to spend their time. This situation raises concerns among parents and their children. Therefore, the implementation of a full-day school program offers a breath of fresh air for parents, encouraging them to choose schools that apply this learning model. The aim of this study is to explore the implementation of a faith-based full-day school program at SD YKPP Pendopo. The research used a qualitative method, with data collection techniques including observation, documentation, and interviews. The results of the study show that it analyzes the implementation of the faith-based full-day school program at SD YKPP Pendopo, focusing on strategies, challenges, and efforts to overcome these challenges. Interviews revealed that strategies to avoid student boredom include the use of varied learning methods, learning media, and the arrangement of seating that considers students’ biological aspects. The full-day school aims to develop students’ intellectual, physical, social, and emotional aspects through a curriculum designed to support their growth. However, there are several obstacles such as student fatigue, limited facilities and infrastructure, and differences in students’ individual characteristics. The strategies to overcome these challenges include varied teaching methods, the use of media, adjusted seating arrangements, and learning outside the classroom. Parental support and teacher creativity are also considered crucial. This study concludes that the implementation of the faith-based full-day school program at SD YKPP Pendopo provides significant benefits but requires appropriate strategies to address emerging challenges.Keywords: Full Day School, Implementation, Religion.